A1 adenosine receptor attenuates intracerebral hemorrhage-induced secondary brain injury in rats by activating the P38-MAPKAP2-Hsp27 pathway. Issue 1 (December 2016) - Zhai, Weiwei; Chen, Dongdong; Shen, Haitao; Chen, Zhouqing; Li, Haiying; Yu, Zhengquan; Chen, Gang
Abstract Background This study was designed to determine the role of the A1 adenosine receptors in intracerebral hemorrhage (ICH)-induced secondary brain injury and the underlying mechanisms. Methods A collagenase-induced ICH model was established in Sprague–Dawley rats, and cultured primary rat cortical neurons were exposed to oxyhemoglobin at a concentration of 10 μM to mimic ICH in vitro. The A1 adenosine receptor agonist N(6)-cyclohexyladenosine and antagonist 8-phenyl-1, 3-dipropylxanthine were used to study the role of A1 adenosine receptor in ICH-induced secondary brain injury, and antagonists of P38 and Hsp27 were used to study the underlying mechanisms of A1 adenosine receptor actions. Results The protein level of A1 adenosine receptor was significantly increased by ICH, while there was no significant change in protein levels of the other 3 adenosine receptors. In addition, the A1 adenosine receptor expression could be increased by N(6)-cyclohexyladenosine and decreased by 8-phenyl-1, 3-dipropylxanthine under ICH conditions. Activation of the A1 adenosine receptor attenuated neuronal apoptosis in the subcortex, which was associated with increased phosphorylation of P38, MAPK, MAPKAP2, and Hsp27. Inhibition of the A1 adenosine receptor resulted in opposite effects. Finally, the neuroprotective effect of the A1 adenosine receptor agonist N(6)-cyclohexyladenosine was inhibited by antagonists of P38 and Hsp27. Conclusions This study demonstrates that activation of the A1 adenosine receptor by N(6)-cyclohexyladenosine could prevent ICH-induced secondary brain injury via the P38-MAPKAP2-Hsp27 pathway.